Trust, Privacy and Security in Digital Business 13th International Conference, TrustBus 2016, Porto, Portugal, September 7-8, 2016, Proceedings - Katsikas, Sokratis; Lambrinoudakis, Costas; Furnell, Steven (Security and Cryptology ;, 2016)
This book constitutes the refereed proceedings of the 13th International Conference on Trust, Privacy and Security in Digital Business, TrustBus 2016, held in Porto, Portugal, in September 2016 in conjunction with DEXA 2016. The 8 revised full papers presented were carefully reviewed and selected from 18 submissions. The papers are organized in the following topical sections: security, privacy and trust in eServices; security and privacy in cloud computing; privacy requirements; and information audit and trust.